Modifikasi Struktur Jetty Pelat Beton Pracetak Konvensional menjadi Pelat Beton Pracetak Hollow Core Slab - Johannes Tarigan; Emma Patricia Bangun; Indra Fischer (Jurnal Syntax Admiration, 2023)
The wharf is where the ships are moored in the harbour. In addition, the pier is also the place where loading and unloading of goods takes place and passengers boarding and falling from and to the ship. The wharf is also the activity location for refueling ships, supplying ships with drinking water, clean water, and arranging channels for dirty/waste water to be further processed at the port. So that optimum planning is needed so that the performance of the building can meet safety and comfort standards This research modifies conventional precast floor slabs into hollow core slab precast slabs with 2 span variations. Dead loads are calculated based on specific gravity, live loads and traffic loads are calculated by "Loading for Bridges" (SNI 1725-2016), crane loads use the Ship to Shore Gantry Cranes Brand Liebherr specifications with a capacity of 50 tons, ship berthing loads and mooring loads ships are calculated based on the Technical standards and commentaries for port and harbor facilities in Japan, OCDI, 2020, while earthquake loads are calculated by "Bridge planning against earthquake loads" (SNI 2833:2016). Steel piles are calculated by "specifications for structural steel buildings" (SNI 1729:2015) and reinforced concrete structures are calculated by “Structural concrete requirements for buildings and explanations” (SNI 2847 2019). Structural analysis for structures is carried out using the help of SAP2000 software. From the research, it was obtained the results of modification of conventional precast floor slabs with hollow core slab precast floor plates with a span of 5.2 meters and a thickness of 350 mm. is an increase in the iron ratio of 38.57% and a decrease in the shear capacity of the punch by 56.57%. For a span of 10.4 meters, a plate with a thickness of 500 mm was used so that the result was an increase in the ratio of iron by 114.60% and a decrease in the shear capacity of the punch by 74.06%.